Platelet production using adipose‐derived mesenchymal stem cells: Mechanistic studies and clinical application - Ono‐Uruga, Yukako (J Thromb Haemost, 2020)
Megakaryocytes (MKs) are platelet progenitor stem cells found in the bone marrow. Platelets obtained from blood draws can be used for therapeutic applications, especially platelet transfusion. The needs for platelet transfusions for clinical situation is increasing, due in part to the growing number of patients undergoing chemotherapy. Platelets obtained from donors, however, have the disadvantages of a limited storage lifespan and the risk of donor‐related infection. Extensive effort has therefore been directed at manufacturing platelets ex vivo. Here, we review ex vivo technologies for MK development, focusing on human adipose tissue‐derived mesenchymal stem/stromal cell line (ASCL)‐based strategies and their potential clinical application. Bone marrow and adipose tissues contain mesenchymal stem/stromal cells that have an ability to differentiate into MKs, which release platelets. Taking advantage of this mechanism, we developed a donor‐independent system for manufacturing platelets for clinical application using ASCL established from adipose‐derived mesenchymal stem/stromal cells (ASCs). Culture of ASCs with endogenous thrombopoietin and its receptor c‐MPL, and endogenous genes such as p45NF‐E2 leads to MK differentiation and subsequent platelet production. ASCs compose heterogeneous cells, however, and are not suitable for clinical application. Thus, we established ASCLs, which expand into a more homogeneous population, and fulfill the criteria for mesenchymal stem cells set by the International Society for Cellular Therapy. Using our ASCL culture system with MK lineage induction medium without recombinant thrombopoietin led to peak production of platelets within 12 days, which may be sufficient for clinical application.